2019
DOI: 10.1039/c9bm00431a
|View full text |Cite
|
Sign up to set email alerts
|

A biomimetic tarso-conjunctival biphasic scaffold for eyelid reconstruction in vivo

Abstract: A biphasic scaffold with bionic structure mimicking tarsus and conjunctiva was manufactured and evaluated in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…However, most recent advances in posterior lamellar reconstruction meet one of the three requirements by using a single tarsal or conjunctival substitute, 6,11,66 undoubtably achieving inferior reconstructive outcomes. Recently, a biphasic scaffold composed of a hard PPF–HEMA layer and a soft collagen/chitosan layer was developed to mimic the bilayered structure of the native posterior lamella 126 . Two weeks after implantation into tarsoconjunctival defects in a rabbit model, the histological findings demonstrated that the hard, porous PPF–HEMA layer supported the shape of the eyelid and allowed the ingrowth of surrounding tissue, while the soft collagen/chitosan sponge layer promoted cell migration and conjunctival regeneration, 126 suggesting the potential of this construct for tarsoconjunctival repair.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most recent advances in posterior lamellar reconstruction meet one of the three requirements by using a single tarsal or conjunctival substitute, 6,11,66 undoubtably achieving inferior reconstructive outcomes. Recently, a biphasic scaffold composed of a hard PPF–HEMA layer and a soft collagen/chitosan layer was developed to mimic the bilayered structure of the native posterior lamella 126 . Two weeks after implantation into tarsoconjunctival defects in a rabbit model, the histological findings demonstrated that the hard, porous PPF–HEMA layer supported the shape of the eyelid and allowed the ingrowth of surrounding tissue, while the soft collagen/chitosan sponge layer promoted cell migration and conjunctival regeneration, 126 suggesting the potential of this construct for tarsoconjunctival repair.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…This copolymerized scaffold was then further modified by depositing a soft collagen/chitosan layer onto the PPF‐HEMA layer to fabricate a biomimetic biphasic scaffold. In a rabbit transconjunctival defect model, this biphasic scaffold allowed tissue to grow inward and maintained the contour of the eyelid, while the collagen/chitosan phase was able to support re‐epithelialization with functional palpebral conjunctiva 126 …”
Section: Acellular Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…They include limited sources, surgical complexity, increased complications, poor mechanical properties, inflammatory immune response, and the spread of potential infectious diseases. Therefore, the in-depth study of new biomaterials and tissue engineering may provide a new perspective for the research of tarsal substitutes due to more flexible biomaterial structures and tissue engineering design (1,2,73).…”
Section: Biomaterials Transplantmentioning
confidence: 99%
“…It is divided into anterior and posterior lamellae by the grey line. The anterior lamella includes the eyelid skin, subcutaneous tissue, and orbicularis oculi muscle, while the posterior consists of the tarsal plate and conjunctiva (2,3). The intact eyelid structure and function are responsible for the stable ocular structure and visual function and necessary for the composition of eye expression.…”
Section: Introductionmentioning
confidence: 99%